Scaling Up Sanitation: Evidence from an RCT in Indonesia - Lisa A. Cameron; Manisha Shah (Institute of Labor Economics (IZA), 2017)
This paper evaluates the effectiveness of a widely used sanitation intervention, Community-Led Total Sanitation (CLTS), using a randomized controlled trial. The intervention was implemented at scale across rural East Java in Indonesia. CLTS increases toilet construction, reduces roundworm infestations, and decreases community tolerance of open defecation. Financial constraints faced by poorer households limit their ability to improve sanitation. We also examine the program's scale up process which included local governments taking over implementation of CLTS from professional resource agencies. The results suggest that all of the sanitation and health benefits accrue from villages where resource agencies implemented the program, while local government implementation produced no discernible benefits.
Keywords: O12; I15; 330; impact evaluation; sanitation; scale up; development; health